Pelatihan Penguatan Perkawinanuntuk Meningkatkan Kepuasan Perkawinan pada Suami Istri Bekerja - Retno Arum Kusumowardhani; Muhammad Nasrul Huda; Adib Ahmad (Personifikasi: Jurnal Ilmu Psikologi, 2017)
A marital enhancement program were designed to improve marital satisfaction among dual-career couples. Subjects were five dual-career couples (10 spouses) in Yogyakarta. Marital enhancement program was a set of activities designed to help couples develop the better functions of their marriage. The program based on aspects of Couples Coping Enhancement Training (CCET) from Bordermann and Shantinanth (2004) and Rosen-Grandon (1999). Marital Satisfaction Scale was used to collect data of marital satisfaction level. The data analysis using t-test showed that there was no difference in marital satisfaction between pretest and posttest, which mean that the marital enhancement program was not effective for this research’s subjects. Some related matters were then discussed.                                        Keywords:Marital enhancement, marital satisfaction, dual-career couples